The association between cigarette smoking attitudes and social capital among Iranian health and medical students: a cross-sectional study - Hamideh Zahedi; Mohammad Hasan Sahebihagh; Parvin Sarbakhsh; Leila Gholizadeh (BMC, 2021)
Abstract Background Smoking remains a leading public health challenge globally. As a psychosocial determinant of health, social capital can influence health attitudes and behaviors, and thus it may have the capacity to reduce smoking rates. The aim of this research was to examine the association between social capital and attitudes towards smoking among university students. Methods This cross-sectional study was conducted among 538 health and medical students, recruited using the proportionate sampling method. Participants' social capital and attitudes toward smoking were assessed using the social capital questionnaire (SCQ) and the scale of cigarette smoking attitude (CSA). Data were analyzed using descriptive statistics, Pearson correlation coefficient, and the multiple regression analysis. Results About one in four health and medical students reported smoking, either currently or in the past, and 30% had either positive or indifferent attitudes towards smoking. The mean scores of the SCQ and the CSA were 105.1 ± 19.7 and 48.6 ± 11.2, respectively. There was a statistically significant negative association between the SCQ and the CSA scores (r = − 0.24; p < 0.001). In the regression analysis, the SCQ scores were also negatively and statistically significantly associated with the CSA scores, after controlling potential confounders (B: -0.09; 95% CI: − 0.13 to − 0.004). Conclusions As future healthcare providers, who are expected to take the primary role in reducing smoking rates in the community, health and medical students should be supported to develop appropriate attitudes towards smoking. Promoting positive social capital among university students has the capacity to improve their attitudes towards smoking. Possessing negative attitudes towards smoking should hopefully reduce smoking behaviors among future health professionals and improve their participation in anti-smoking campaigns.